A comparative test of different density functionals for calculations of NH3-SCR over Cu-Chabazite. Issue 21 (15th May 2019) - Chen, Lin; Janssens, Ton V. W.; Grönbeck, Henrik
Abstract : A general challenge in density functional theory calculations is to simultaneously account for different types of bonds. Here, different exchange–correlation functionals are explored for O2 dissociation over Cu(NH3 )2 + complexes in Cu-Chabazite. Abstract : A general challenge in density functional theory calculations is to simultaneously account for different types of bonds. One such example is reactions in zeolites where both van der Waals and chemical bonds should be described accurately. Here, we use different exchange–correlation functionals to explore O2 dissociation over pairs of Cu(NH3 )2 + complexes in Cu-Chabazite. This is an important part of selective catalytic reduction of NO x using NH3 as a reducing agent. The investigated functionals are PBE, PBE+ U, PBE+D, PBE+ U +D, PBE-cx, BEEF and HSE06+D. We find that the potential energy landscape for O2 activation and dissociation depends critically on the choice of functional. However, the van der Waals contributions are similarly described by the functionals accounting for this interaction. The discrepancies in the potential energy surface are instead related to different descriptions of the Cu–O chemical bond. By investigating the electronic, structural and energetic properties of reference systems including bulk copper oxides and (Cu2 O2 ) 2+ enzymatic crystals, we find that the PBE+ U approach together with van der Waals corrections provides a reasonable simultaneous accuracy of the different bonds in the systems.